Pemanfaatan Lingkungan Sekitar Sebagai Sumber Belajar Dalam Memahami Pembelajaran Ekonomi pada Siswa Kelas VI UPT SDN 29 Majannang - Sumiati T; Muh Yunus; Rego Devilla; Erni Rismawanty (QISTINA: Jurnal Multidisiplin Indonesia, 2026)
This study aims to analyze the effectiveness of environment-based economics learning in improving the understanding of sixth-grade students at UPT SDN 29 Majannang, Bungoro District, Pangkep Regency. In addition, this study seeks to identify the challenges faced by teachers in implementing the use of the surrounding environment as a learning resource in economics education. The utilization of local environmental potential is expected to bridge the gap between abstract economic concepts and the students’ real-life experiences. This research employed a qualitative research method with a case study approach. The research subjects consisted of sixth-grade students and economics teachers at UPT SDN 29 Majannang. Data were collected through in- depth interviews, participatory observation, and documentation studies. Data validity was ensured through source and method triangulation as well as member checking. Data analysis was conducted through stages of data collection, coding, categorization, interpretation, and descriptive presentation of findings. The results indicate that the utilization of the surrounding environment as a learning resource in economics can enhance students’ conceptual understanding, particularly regarding the concepts of production, distribution, and consumption. Students became more active, enthusiastic, and capable of relating learning materials to real conditions in their environment. However, the implementation of environment-based learning has not been carried out optimally and sustainably due to constraints such as limited instructional time, lack of structured lesson planning, and teachers’ concerns regarding student safety. These findings suggest that environment-based economics learning has significant potential to improve the quality of learning when supported by careful planning and adequate institutional support.